2022
DOI: 10.1111/1749-4877.12647
|View full text |Cite
|
Sign up to set email alerts
|

Seasonal changes in the parasite prevalence of a small Malagasy lemur species (Lepilemur edwardsi)

Abstract: Parasitic infections can impact the fitness of individuals and can have influence on animals' population dynamics. An individuals' parasite prevalence often changes depending on external or seasonal changes, for example, rainfall and ambient temperatures, but also on internal changes, for example, changes in body condition. In this study we aimed to identify the environmental factors that may influence the intestinal parasite and ectoparasite prevalence of the folivorous Malagasy primate species, Lepilemur edw… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 62 publications
(153 reference statements)
0
4
0
Order By: Relevance
“…Sportive lemurs inhabit almost all habitats in Madagascar and can survive even in the driest and harshest environments on this island, such as the extremely dry spiny forests in southern Madagascar and the seasonal deciduous dry forests in the West. However, individuals seem to be affected by the unfavorable conditions of the dry season, as previous studies show that L. edwardsi increases its resting metabolism to cope with these conditions and has a higher parasite prevalence towards the end of the dry season (Bethge et al, 2021(Bethge et al, , 2022.…”
Section: Discussionmentioning
confidence: 99%
“…Sportive lemurs inhabit almost all habitats in Madagascar and can survive even in the driest and harshest environments on this island, such as the extremely dry spiny forests in southern Madagascar and the seasonal deciduous dry forests in the West. However, individuals seem to be affected by the unfavorable conditions of the dry season, as previous studies show that L. edwardsi increases its resting metabolism to cope with these conditions and has a higher parasite prevalence towards the end of the dry season (Bethge et al, 2021(Bethge et al, , 2022.…”
Section: Discussionmentioning
confidence: 99%
“…Observing the feeding behavior of the wild Tibetan macaques in the future may understand the effect of Euphorbiaceae or other plants on parasite infection. In addition, the study on lemur (Lepilemur edwardsi) in Madagascar found that the differences in prevalence rates of intestinal parasites between the wet and dry seasons might be due to the accompanying decrease in diet quality (Bethge et al, 2022). According to another research, wild rhesus macaques living in high-altitude consume more roots and fallen leaves during winter to respond the food scarcity (K. Zhang et al, 2022).…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of intestinal parasites is not only related to the health status of the host but also in uenced by climatic factors such as temperature, rainfall, and altitude (Turner et al, 2012;Sanchez et al, 2018;Yu et al, 2023). The climatic factors may further cause seasonal differences in the prevalence of parasites, which were reported in a previous study on the lemurs in Madagascar (Bethge et al, 2022), and the Tibetan macaques of Mount Emei in Sichuan, China (Yang et al, 2022). Tibetan macaques are endemic primates in China and are distributed in the central and southern regions of China (JIANG Xue-long, 1996).…”
Section: Introductionmentioning
confidence: 94%
“…However, this is somewhat inconsistent with a previous coprological study of parasites in the same population (Parr et al, 2013b), which found 7 helminth morphotypes in both the wet and dry seasons. The inconsistencies in the results of parasitological studies at the Santa Rosa field site are not unique as the primate parasitology literature is generally mixed on whether environmental conditions and seasonality strongly influence parasitic infections (e.g., Akinyi et al, 2019;de Winter et al, 2020;Blersch et al, 2021;Bueno de Mesquita et al, 2021;Bethge et al, 2022). However, conclusions are likely confounded by differences in study design, sampling, analyses, host-parasite relationships, and site-specific factors.…”
Section: Seasonality and 18s Diversitymentioning
confidence: 99%